Development of Parkinson Disease and Its Relationship with Incidentally Discovered White Matter Disease and Covert Brain Infarction in a Real‐World Cohort. Issue 4 (17th August 2022) - Kent, David M.; Leung, Lester Y.; Puttock, Eric J.; Wang, Andy Y.; Luetmer, Patrick H.; Kallmes, David F.; Nelson, Jason; Fu, Sunyang; Zheng, Chengyi; Vickery, Ellen M.; Liu, Hongfang; Noyce, Alastair J.; et al.
Abstract : Objective: This study aimed to examine the relationship between covert cerebrovascular disease, comprised of covert brain infarction and white matter disease, discovered incidentally in routine care, and subsequent Parkinson disease. Methods: Patients were ≥50 years and received neuroimaging for non‐stroke indications in the Kaiser Permanente Southern California system from 2009 to 2019. Natural language processing identified incidentally discovered covert brain infarction and white matter disease and classified white matter disease severity. The Parkinson disease outcome was defined as 2 ICD diagnosis codes. Results: 230, 062 patients were included (median follow‐up 3.72 years). A total of 1, 941 Parkinson disease cases were identified (median time‐to‐event 2.35 years). Natural language processing identified covert cerebrovascular disease in 70, 592 (30.7%) patients, 10, 622 (4.6%) with covert brain infarction and 65, 814 (28.6%) with white matter disease. After adjustment for known risk factors, white matter disease was associated with Parkinson disease (hazard ratio 1.67 [95%CI, 1.44, 1.93] for patients <70 years and 1.33 [1.18, 1.50] for those ≥70 years). Greater severity of white matter disease was associated with increased incidence of Parkinson disease(/1, 000 person‐years), from 1.52 (1.43, 1.61) in patients without white matter disease to 4.90 (3.86, 6.13) in those with severe disease. Findings were robust when more specific definitions of Parkinson disease were used. Covert brain infarction was not associated with Parkinson disease (adjusted hazard ratio = 1.05 [0.88, 1.24]). Interpretation: Incidentally discovered white matter disease was associated with subsequent Parkinson disease, an association strengthened with younger age and increased white matter disease severity. Incidentally discovered covert brain infarction did not appear to be associated with subsequent Parkinson disease. ANN NEUROL 2022;92:620–630